2000
DOI: 10.1037/0022-0663.92.2.342
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' coaching of learning and its relation to students' strategic learning.

Abstract: This study examined types and frequency of coaching of learning at the middle school level and its relation to students ' strategic learning. Teachers (n = 11) were videotaped during daily instruction on 3 separate occasions, and students (n = 235) responded to a self-report questionnaire about learningstrategy use. Consistent with previous research at the elementary level (E. B. Moely et al., 1992). average instances of teachers' coaching of learning (e.g., describing cognitive processes, suggesting strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 21 publications
5
46
1
5
Order By: Relevance
“…According to Waeytens et al (2002), teachers lack knowledge about the concept of self-regulated learning. Observation studies also showed that they spend only little of their instruction time on strategy teaching (Hamman et al 2000). Therefore, when implementing an intervention to promote self-regulated learning by the regular teachers, extensive teacher training would be necessary.…”
Section: Drawing Inferences From the Resultsmentioning
confidence: 98%
“…According to Waeytens et al (2002), teachers lack knowledge about the concept of self-regulated learning. Observation studies also showed that they spend only little of their instruction time on strategy teaching (Hamman et al 2000). Therefore, when implementing an intervention to promote self-regulated learning by the regular teachers, extensive teacher training would be necessary.…”
Section: Drawing Inferences From the Resultsmentioning
confidence: 98%
“…Although either a repeated measure analysis 12 or the paired Student t test should be used, our survey responses were anonymous; hence, we were unable to link the survey instruments completed before and after the course by any identifiers. We also treated the responses to the MSLQ as parametric data since it is usual practice to treat these data as such, as has been demonstrated in numerous published reports using the MSLQ, [12][13][14][15] despite the ordinal nature of the Likert scale. For our secondary objectives, we performed descriptive statistics on students' feedback of the course, as well as the completion rate of optional assignments.…”
Section: Discussionmentioning
confidence: 99%
“…Moely et al (1992) used an observation instrument to investigate elementary school teachers' promotion of learning strategies in language and mathematics lessons. Hamman et al (2000) focused on the middle school level and applied a similar observation scheme to examine strategy instruction in lessons of different subjects. The results of both studies indicate that teachers spend only a small amount of their instructional activity on teaching students how to learn effectively.…”
Section: Assessing the Promotion Of Self-regulated Learningmentioning
confidence: 99%